Reducing Carbon Footprint and Costs in Healthcare: The Impact of Reverting to Pre-COVID Waste Management Practices - Hendry, Anna; Liang, Emily; Barthelmes, Ludger; Haughan, Michelle (Impact Surgery, 2025)
Background: Approximately 5% of NHS emissions are caused by waste and water use. During the COVID-19 pandemic, low-cost, energy-efficient waste streams were replaced with more energy- and carbon-intensive alternatives. After the pandemic, these changes were not reversed, leading to increased environmental and financial impacts. Methods: A 24-hour baseline audit of waste streams was conducted on a ward, categorizing waste into dry recycling, domestic, tiger-striped offensive, and clinical waste. Costs and equivalent carbon dioxide (eCO2) emissions were calculated based on the weight of each waste stream. In collaboration with infection control, waste streams were reverted to pre-COVID arrangements. A second audit was performed to reassess waste production, costs, and eCO2 emissions after implementation of the changes. Results: The baseline audit revealed no dry recycling and 5 kg of domestic waste, alongside 42.5 kg of offensive and 5 kg of clinical waste. After reverting to pre-COVID waste streams, dry recycling increased, while offensive and clinical waste production decreased significantly, leading to reduced costs and eCO2 emissions. Clinical waste, the most expensive and carbon-intensive stream, was halved, and the domestic-to-offensive waste ratio decreased by 0.8. Extrapolating these changes across the trust, we estimated annual savings of over £20,000 and a reduction of 17,000 kg eCO2. Conclusion: Reverting to pre-COVID waste management practices demonstrated substantial financial and carbon savings. These findings highlight the importance of sustainable waste management in reducing environmental impact and optimizing healthcare costs.